Aggregation, acidochromicity, and metallochromicity of a pyridine-based poly(aryleneethynylene) - Seehafer, Kai; Bender, Markus; Bunz, Uwe H. F. (Macromolecules, 2014)
A pyridine-containing poly(aryleneethynylene) (PAE) is investigated, showing surprisingly versatile changes of its photophysical properties in response to external stimuli. Because of agglomeration-induced planarization of the backbone, this PAE exhibits a significant red-shift in absorption and emission, when moving from good to poor solvents. The basic lone pair on the pyridine unit makes this PAE pH-sensitive and imparts metallochromic properties, useful for the potential detection of a wide range of metal cations, resulting in color responses that range from quenching to red-shifted emission.